Transforming Quranic Learning in Islamic Boarding Schools through the Visual, Auditory, and Kinesthetic-Based Wafa Method - Listyamarta Furwaningsih; Syamsul Arifin; Azid Syukroni (Institut Agama Islam An-Nawawi Purworejo, 2026)
This study examines the ability to read the Quran correctly according to Tajwid rules as a fundamental competence that every student must possess. However, constraints such as fatigue from conventional methods and differing initial abilities often become obstacles. This research aims to analyze the effectiveness of implementing the Wafa method in improving the Quran reading quality of students at Al-Madinah Islamic Boarding School in Ponorogo. This research employs a qualitative approach with a case study design. Data were collected through observations, in-depth interviews, and documentation. The results show that the Wafa method is effective in improving the Quran reading quality of students, particularly in the accuracy of makharijul huruf (letter articulation) pronunciation, understanding of Tajwid rules, and reading fluency (fashahah). This improvement is supported by the use of a right-brain-based approach combined with Hijaz rhythm and multisensory learning involving visual, auditory, and kinesthetic aspects. This approach can create a more interesting learning atmosphere, thereby reducing the fatigue level of students during the learning process. The implementation of the Wafa method is carried out through a 5P learning cycle that includes opening, experience, teaching, assessment, and closure systematically. The successful implementation of this method is also supported by the presence of certified educators, as well as daily monitoring and periodic evaluations to objectively track student progress. In addition to providing an impact on improving the ability to read the Quran, this research also found positive influences on the psychological aspects of students, such as increased self-confidence, learning motivation, and emotional closeness to the Quran. Nevertheless, the implementation of the Wafa method still faces several obstacles, including student fatigue due to dense activities in the boarding school, difficulties in adapting to the use of Hijaz rhythm for new students, and limitations in facilities and learning funding. Overall, the Wafa method proves to be an effective Quran learning innovation because it not only improves reading quality technically but also contributes to character building and strengthening the emotional attachment of students to the Quran.